The Influence of 3K (Knowledge Acquisition, Knowledge Sharing, and Knowledge Implementation) on Administrative Innovation in Government Institution (A Case Study: Direktorat Bela Negara Ditjen Pothan Kemhan) - Achmad Ghazali (Jurnal Ilmiah Mahasiswa FEB, 2020)
This study was aimed to determine the effect of knowledge acquisition, knowledge sharing, and knowledge implementation towards administrative innovation on government institutions, particularly in the Ministry of Defense (Kemhan). In the emergence of new practices and technologies, innovation becomes an important aspect to explore for the organization to thrive. Furthermore, knowledge plays a pivotal role in shaping the innovation itself. The process of acquiring new knowledge, sharing and developed, and implemented knowledge becomes a routine in an organization that seeks innovation. With the unprecedented events of COVID-19 in 2020, it becomes apparent that the organization needs to be more innovative to cater new normal of living. This study investigated whether knowledge acquisition, knowledge sharing, and knowledge implementation have a significant influence on administrative innovation in the Kemhan organization. The independent variables include knowledge acquisition (X1), knowledge sharing (X2), and knowledge implementation (X3), while the dependent variable is administrative innovation (Y). Quantitative approach and explanatory research with a few hypotheses were employed. Data were collected through an online questionnaire with 5-likert scale. The 120 respondents were taken from two divisions of Kemhan. The data were analyzed using the Multiple Linear Regression method, t-test for hypothesis testing, and assisted by IBM SPSS v25.0 for Windows 10 as analysis tools. Results indicated that knowledge acquisition, knowledge sharing, and knowledge implementation have a significant positive influence on administrative innovation.Keywords: knowledge acquisition, knowledge sharing, knowledge implementation, administrative innovation